Indissolubilitas... quae ratione sacramenti peculia rem obtinet firmitatem (kan. 1056). Uwagi o relacji nierozerwalność – sakrament małżeństwa - Pastwa, Andrzej (Śląskie Studia Historyczno-Teologiczne, 2011)
This paper is based on the following statement of Pope Benedict XVI taken from his address to the Roman Rota on the Indissolubility of Marriage (29 January 2010): “...existential, person-centered and relational consideration of the conjugal union can never be at the expense of indissolubility, an essential property which, in Christian marriage, obtains, with unity, a special firmness by reason of the sacrament (cf. CIC, can. 1056)”. The essential message of Pope Benedict XVI can be expressed in this way: In our days the rule of indissolubility of marriage, rooted in the mystery of Creation and Redemption, is obscured and distorted. This fact creates the urgent need for deeper reflection on the relationship between indissolubility and sacrament. More precisely, having in mind renewed anthropology, it is necessary to find an answer to the question: How to understand firmitas? – the key category of the canonical norm quoted by the Pope. The magisterium of Pope Benedict XVI, especially his speeches to the Roman Rota (2006-2010), allows for the formulation of a thesis on the genetic foundation of the sacramental dimension of marriage in the “lifelong” character of union between man and woman. Consequently the indissolubility (essential quality of marriage) – seen in a personal and historical perspective of consortium totius vitae–appears as an institutional expression of the power of the bond of the “covenant of conjugal love”.